1998
DOI: 10.1177/002215549804601207
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Antibodies to Nitric Oxide Synthase Isoforms in Human, Guinea Pig, Rat, and Mouse Tissues

Abstract: SUMMARYTen commercially available rabbit polyclonal anti-NOS antibodies were tested for their immunohistological applicability in normal human, guinea pig, rat, and mouse organs. Most antibodies reacted as expected and described in the literature with various tissues of the investigated species. Several antibodies did not react with the expected cell populations in a certain species, or reacted in previously unknown patterns. In addition, different antibodies to the same isoform rarely detected identical cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 19 publications
3
42
0
1
Order By: Relevance
“…Although no quantitative description about the density of nNOS-IR neurons in the hippocampus has been previously reported, there appears to be a greater number of nNOS-IR neurons in the present study than reported by others. The mouse monoclonal anti-nNOS antibody used has been shown to react specifically with the 150-kDa human nNOS of the recombinant protein or brain extract (Western blot), showing sufficient isoform specificity to undertake reliable immunohistochemical staining (30). We may have observed a greater density because previous studies used different fixation techniques (formalin-fixed tissue versus frozen sections) and detected nNOS expression using polyclonal antibodies or NADPH-diaphorase histochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Although no quantitative description about the density of nNOS-IR neurons in the hippocampus has been previously reported, there appears to be a greater number of nNOS-IR neurons in the present study than reported by others. The mouse monoclonal anti-nNOS antibody used has been shown to react specifically with the 150-kDa human nNOS of the recombinant protein or brain extract (Western blot), showing sufficient isoform specificity to undertake reliable immunohistochemical staining (30). We may have observed a greater density because previous studies used different fixation techniques (formalin-fixed tissue versus frozen sections) and detected nNOS expression using polyclonal antibodies or NADPH-diaphorase histochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for this disagreement is the wide heterogeneity of the experimental models studied so far. Additional discrepancy may arise from the fact that the primary antibodies used to detect iNOS come from several sources, because the behavior of different antibodies directed against NOS isoforms can vary dramatically according to type (monoclonal versus polyclonal), species in which the antibody was raised, and tissue in which the antibody is tested (19).…”
mentioning
confidence: 99%
“…Recent work 45,46 suggested that a novel mechanism involving iNOS ubiquitination and proteasomic proteolysis could also play a role in the regulation of iNOS activity. As previously proposed by Zhao et al 21 and Coers et al, 47 the small molecular weight bands revealed by Western blot could be considered as proteolytic degradation products. However, further work in this direction should be performed in order to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 52%